Remote Experiments, from Internet to Intranet - KOZÍK, Tomáš; KUNA, Peter; ŠIMON, Marek; ARRAS, Peter (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2015)
Remote experiments for teaching purposes are mediated by users, especially on the Internet. To access a remote experiment from within the universities, the intranet is also used. In terms of extending the application of remote experiments, an interesting method is the creation of community networks on the Internet with associations of educational institutions. In this article authors focused their attention on the formulation and application of remote experiments in education, in terms of their availability on the Internet and Intranet.